2021
DOI: 10.3390/cancers13081892
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rh1 Induces MCF-7 Cell Apoptosis and Autophagic Cell Death through ROS-Mediated Akt Signaling

Abstract: Breast cancer (BC) is the leading cause of cancer-related deaths among women worldwide. Ginsenosides exhibit anticancer activity against various cancer cells. However, the effects of ginsenoside Rh1 on BC and the underlying mechanisms remain unknown. Here, we investigated the anticancer effects of Rh1 on human BC MCF-7 and HCC1428 cells and the underlying signaling pathways. The anticancer effects of Rh1 in vitro were evaluated using sulforhodamine B (SRB), 3-(4, 5-dimethylthiazole-2-yl)-2, 5-diphenyltetrazoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 56 publications
2
27
0
Order By: Relevance
“…After 48 h, the culture medium was removed and cells were washed with 1× PBS one time beforebeing stained with propidium iodide test kit obtained from Beyotime Biotechnology Company. Afterward, the cells were observed, and images were captured using a fluorescence microscope at 100× magnification (Huynh et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…After 48 h, the culture medium was removed and cells were washed with 1× PBS one time beforebeing stained with propidium iodide test kit obtained from Beyotime Biotechnology Company. Afterward, the cells were observed, and images were captured using a fluorescence microscope at 100× magnification (Huynh et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The damage of ROS to cells is primarily reflected in the damage to biomacromolecules, such as oxidative damage to DNA, proteins, and biofilms [32] . An increasing number of reports indicate that reactive oxygen species have a critical function in the induction of apoptosis and autophagy [33] , [34] . Moreover, reactive oxygen species affect multiple signaling pathways [35] .…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, ROS is a kind of by-product of cellular metabolism, which contributes to many vital biological processes, including autophagy and apoptosis as well as cell cycle arrest in various human cancer cell lines [ 40 , 41 ]. Recently, a study conducted by Zhang et al has demonstrated that ROS can stimulate Akt/p38 MAPK pathway directly in vitro , thereby mediating cell cycle arrest and apoptosis in human hepatoma cells [ 17 ].…”
Section: Discussionmentioning
confidence: 99%